Regulation of Psychostimulant-induced Signaling and Gene Expression in the Striatum - McGinty, Jacqueline F. (2008)
Amphetamine and cocaine are indirect dopamine agonists that activate multiple signaling cascades in the striatum. Each cascade has a different subcellular location and duration of action that depend on the strength of the drug stimulus. In addition to activating D1 dopamine-Gs-coupled-protein kinase A signaling, acute psychostimulant administration activates extracellular-regulated kinase transiently in striatal cells; conversely, inhibition of extracellular-regulated kinase phosphorylation decreases the ability of psychostimulants to elevate locomotor behavior and opioid peptide gene expression. Moreover, a drug challenge in rats with a drug history augments and prolongs striatal extracellular-regulated kinase phosphorylation, possibly contributing to behavioral sensitization. In contrast, amphetamine activates phosphoinositide-3 kinase substrates, like protein kinase B/Akt, only in the nuclei of striatal cells but this transient increase induced by amphetamine is followed by a delayed decrease in protein kinase B/Akt phosphorylation whether or not the rats have a drug history, suggesting that the phosphoinositide-3 kinase pathway is not essential for amphetamine-induced behavioral sensitization. Chronic amphetamine or cocaine also alters the regulation of inhibitory G-protein-coupled receptors in the striatum, as evident by a prolonged decrease in the level of regulator of G protein signaling 4 after non-contingent or contingent (self-administered) drug exposure. This decrease is exacerbated in behaviorally-sensitized rats and reversed by re-exposure to a cocaine-paired environment. A decrease in regulator of G protein signaling 4 levels may weaken its interactions with metabotropic glutamate receptor 5, Gαq, and phospholipase C β that may enhance drug-induced signaling. Alteration of these protein-protein interactions suggests that the striatum responds to psychostimulants with a complex molecular repertoire that both modulates psychomotor effects and leads to longterm neuroadaptations.